Blood cell alterations in Colossoma macropomum juveniles caused by silver nanoparticles - JULIANA O. MENESES; FERNANDA DOS SANTOS CUNHA; JOEL ARTUR R. DIAS; NATALINO DA COSTA SOUSA; MÁRCIA VALÉRIA S. DO COUTO; ANA FLÁVIA S. DA CUNHA; PETERSON EMMANUEL G. PAIXÃO; HIGO A. ABE; VICTOR RUAN S. NASCIMENTO; JULIANA C. CARDOSO; LUIZ P. DA COSTA; RODRIGO Y. FUJIMOTO (Anais da Academia Brasileira de Ciências, 2024)
Abstract This study evaluated the median lethal concentration of silver nanoparticles and their effects in fish tambaqui Colossoma macropomum. Therefore, an acute toxicity assay was carried out in completely randomized design evaluating six different concentrations of silver nanoparticles on blood parameters of tambaqui. The silver nanoparticles were produced by chemical reduction with polyvinyl alcohol (AgNP-PVA). The lethal concentration 50% (LC50) was estimated using probit regression. The blood was collected, analyzed and the data were submitted to T-test (dying x surviving fish) and Tukey test (surviving fish). An increase in glucose, hematocrit, total plasma protein, hemoglobin, erythrocytes, leukocytes, monocytes, and neutrophils as well as reduced MCV (mean corpuscular volume) in dying fish compared to surviving fish were observed. Survived fish exposed to 187.5 µg/L showed an increase in hematocrit, MCV, and MCH and a reduction in erythrocytes, total numbers of leukocyte, thrombocyte, lymphocyte, and neutrophil. The fish exposed to concentrations below 125 µg/L, had returned the blood parameter to baselines compared to control. The estimated LC50 was 165.09 µg/L and was classified as highly toxic for the fish tambaqui. In higher concentrations, it causes an acute respiratory toxicity, but in concentrations below 125 µg/L, the fish can adapt to the stressing agent.